Diagnosing the reality of applying the operating requirement according to the international specification for the business continuity management system (ISO 22301:2019) : applied research in the General Tax Authority (Journal of Accounting and Financial Studies ( JAFS ), 2023)
Abstract                 The research aims to diagnose the reality of applying the eighth requirement (operation) of the business continuity management system according to the international standard (ISO 22301: 2019), in the General Tax Authority, which is related to planning, implementing and controlling specific processes and procedures to address risks and opportunities, and the research adopted the checklist of the standard ( ISO 22301: 2019), in obtaining information, to measure the extent of application and documentation, the percentages and the weighted arithmetic mean were relied upon, and the research reached a set of results, the most prominent of which was that the level of application and documentation of this requirement amounted to (7%), i.e. a gap of (93%), and this does not achieve the required degree of conformity with the requirement in the international standard, so it requires the researched body to address the gaps by making improvements and reviewing the system to reduce these gaps.